Sulfoethylation of polysaccharides—A comparative study. (15th October 2020) - Gabriel, Lars; Koschella, Andreas; Tied, Antje; Pfeifer, Annett; Heinze, Thomas
Graphical abstract: Highlights: Heteropolysaccharides exhibited higher degrees of substitution than others. Some sulfoethyl polysaccharides remained soluble in dimethyl sulfoxide. A 2 % slurry of polysaccharides with 25 % NaVS solution afforded highest DS values. Sulfoethyl cellulose with DS 1.51 using 4 consecutive sulfoethylation steps. Abstract: The heterogeneous sulfoethylation of cellulose, xylan, α-1, 3-glucan, glucomannan, pullulan, curdlan, galactoglucomannan, and agarose was studied using sodium vinylsulfonate (NaVS) as reagent in presence of sodium hydroxide and iso -propanol ( i -PrOH) as slurry medium. The influence of the concentration of polymer, water, and NaOH (solid or aqueous solution) on the degree of substitution (DS) was investigated. The sulfoethylation rendered the polysaccharides studied water-soluble. Sulfoethylation of heteropolysaccharides yielded products with higher DS compared to the conversion of homopolysaccharides. Structure characterization was carried out by means of 13 C-NMR spectroscopy.